Effect of patient satisfaction on the utilization of mHealth services by patients with chronic disease - Jiao Lu; Heng Zhao; Zhilin Ji; Yanan Dong (Digital Health)
Background Mobile health (mHealth) is considered an effective way to manage chronic disease patients’ health. However, patients often do not use or continue using mHealth services due to concerns about service quality. Patient satisfaction may influence their utilization, and this effect may be moderated by platform regulations and differences in physicians’ qualifications and regions. Objective This study aims to enhance mHealth service utilization by examining how patient satisfaction affects both use and continuous use behaviors. It also explores the role of platform regulations (recommendation, commenting, and reward systems) and assesses differences due to physician proficiency and regional variations. Methods Data were collected from Haodf, a leading mHealth platform in China, from October 2021 to March 2022 at 3-month intervals. Generalized additive models were used to verify nonlinear relationships between patient satisfaction and their utilization behaviors. The role of platform regulations and heterogeneity analysis regarding physician region was also examined. Results Efficacy satisfaction positively influenced mHealth service utilization ( p  < 0.01), while efficacy and attitude satisfaction positively influenced continuous use ( p  < 0.01). Platform regulations altered these relationships ( p  < 0.01). Comprehensive recommendations had a greater effect than patient recommendations ( p  < 0.01). High-quality evaluations played a significant role ( p  < 0.01), while nonmaterial rewards had no significant effect ( p  ≥ 0.05). These relationships varied by physician region ( p  < 0.01). Conclusions Efficacy satisfaction drives mHealth service utilization, while efficacy and attitude satisfaction drive continuous use. Recommendation and commenting systems exhibit a positive synergistic effect, while the reward system plays a supplementary role. Professional recommendations and high-quality evaluations enhance the evaluation system's reliability, promoting service utilization. Patients in big cities are more sensitive to physicians’ proficiency and therapeutic effects. A multidimensional, transparent evaluation and feedback system should be integrated into the platform to improve service quality and increase patient utilization and loyalty.